Barndomsbilder i förändring i grundskolans läseböcker - Angerd Eilard (Educare)
The article explores how norms and ideals linked to generation, gender and ethnicity are expressed in school readers used in Swedish schools since 1962, the year of the first national curriculum of the compulsory school. More than 60 readers have been examined. The adopted perspective combines a genealogical and a critical multimodal discourse analytical approach with an intersectional perspective. This means that the readers’ texts and illustrations are viewed as a whole and as social constructions in the historical context of their periods. Accordingly, the way changes in the late modern society, regarding childhood and family, are depicted in the readers are made visible, as well as the inclusion and exclusion of certain social subjects. Although the contemporary readers appear to advocate diversity and equal opportunities the analysis shows that a colonial white Western, as well as a heteronormative, discourse remains comparatively unchanged throughout the period. The most noticeable finding is the reversed generation hierarchies that characterize the late books. A striking point here is that the old nuclear family has been replaced by an ideal of young heterosexual twosomeness.